2004
DOI: 10.1080/14733140412331384068
|View full text |Cite
|
Sign up to set email alerts
|

The hardest words: Exploring the dialogue of suicide in the counselling process — A discourse analysis

Abstract: Increasing suicide rates among specific groups of the population have led to the publication of suicide reduction targets and guidelines applicable to all mental health professionals, including counsellors. It is now widely expected that mental health workers possess skills and knowledge in the assessment of suicide risk. This research study used a discourse analysis approach to analyse 16 counselling transcripts generated from assessment interviews with suicidal ‘client actors’. Clients generally only referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…Research indicates that many mental health professionals (Reeves, Bowl, Wheeler, & Guthrie, 2004) and medical professionals (Earls, 1989) shy away from asking clients directly about suicide; even being able to ask about suicidal thoughts requires uncommon skill and comfort with the topic (Shea, 1999). It is encouraging that almost one third of teachers, many of whom never received training in suicide prevention, had taken it upon themselves to directly ask students about suicidal thoughts or behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…Research indicates that many mental health professionals (Reeves, Bowl, Wheeler, & Guthrie, 2004) and medical professionals (Earls, 1989) shy away from asking clients directly about suicide; even being able to ask about suicidal thoughts requires uncommon skill and comfort with the topic (Shea, 1999). It is encouraging that almost one third of teachers, many of whom never received training in suicide prevention, had taken it upon themselves to directly ask students about suicidal thoughts or behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…Studies that involved post-session analysis of metaphoric content by therapist and client indicated that the client and therapist often had different understandings of metaphor meaning (Angus & Rennie, 1988;Rasmussen & Angus, 1996). A poignant example of this misunderstanding is evident in a critical discourse analysis of single session transcripts in which Reeves, Bowl, Wheeler, and Guthrie (2004) demonstrated that few counsellors responded directly to clients' metaphoric responses about suicide with an assessment of severity or intent Downloaded by [University of Connecticut] at 12:13 11 October 2014…”
Section: Application To Assessmentmentioning
confidence: 94%
“…Collins & Cutcliffe (2003) assert that most suicidal clients are seeking a therapeutic relationship that will bring them hope and reverse the trajectory towards death. This position demands that attempts should be made to restore hope through engagement, rather than confirm despair through non‐intervention (Reeves et al . 2004).…”
Section: Irrationality and Hopelessnessmentioning
confidence: 99%